Analyze the Relationship Between Investment and the Economic Growth of Lao PDR - BOUNYAVONG, Phetmanivone; CHANTHAVONE, Thongphanh; XIONGTOUA, Tongvang (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
The aim of this study is to analyze the relationship between public and private investment and economic growth in the Lao People's Democratic Republic. The time series data from 2001-2023 was used and a VAR model was employed to analyze the relationship. The results of the analysis showed that economic growth in the previous year and private investment had the positive effect on economic growth, with a statistical significance level of 0.01 and 0.1 respectively, and consistent with the hypothesis which economic growth having a greater effect than private investment. Holding other factors constant, current economic growth increased or decreased by 0.62% in the same direction if economic growth in the previous year increased or decreased by 1%. Public investment in the previous year also influenced current public investment with a statistical significance level of 0.05 and in accordance with the hypothesis, i.e. if public investment increased or decreased by 1% in the previous year, current public investment increased or decreased by 0.63% in the same direction. It was also found that economic growth in the previous year affected private investment in the same direction, with a significance level of 0.01 and consistent with the hypothesis that, if economic growth in the previous year increases or decreases by 1%, private investment increases or decreases by 0.72% in the same direction.